1 & 2 Kronieke as "n magsteks - Geyser, A. B. (HTS teologiese studies, 2006)
1 & 2 Chronicles – a discourse of powerThis study compares Chronicles with its source documents. It is obvious that the authors of Chronicles omitted certain parts of the source documents on the other hand on the other emphasized certain aspects with a specific purpose. The result is that the Southern kingdom receives a positive evaluation, while the Northern kingdom is described in a negative light. David is presented as the ideal king and in contrast to Exodus is credited as the founder of the religious cult. The cult in Jerusalem is legitimized and proclaimed as the only true religion. In so doing the books of Chronicles without a doubt secured and legitimized the position and actions of the temple personnel. As long as the temple existed it functioned as a discourse of power within this community. As a discourse of power, it set boundaries and excluded different groups that were traditionally part of the people of YHWH. The destruction of the temple though, disempowered this text and opened up the way for it to become part of the Hebrew canon.